1992
DOI: 10.1002/mds.870070313
|View full text |Cite
|
Sign up to set email alerts
|

Dystonia following head trauma: A report of nine patients and review of the literature

Abstract: We report nine patients who developed dystonia following head trauma. The most frequent form was hemidystonia only (six patients). One patient presented with hemidystonia plus torticollis, one with bilateral hemidystonia and one with torticollis only. Seven patients sustained a severe head injury, and two had a mild head injury. At the time of injury, six were younger than 10 years, two were adolescents, and the patient with torticollis only was an adult. Except in the patient with torticollis only, the onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
6

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(49 citation statements)
references
References 48 publications
0
43
0
6
Order By: Relevance
“…5) [11, 12], and these arteries are functional end arteries. The territory of this branch is thus mechanically vulnerable to ischemia as a result of vascular occlusion or mechanical spasm following arterial disruption, even following mild head injury [1, 3,13,14,15]. In the present case, recurrent episodes of transient but reversible hemiparesis would be consistent with intermittent arterial spasm.…”
Section: Discussionmentioning
confidence: 55%
“…5) [11, 12], and these arteries are functional end arteries. The territory of this branch is thus mechanically vulnerable to ischemia as a result of vascular occlusion or mechanical spasm following arterial disruption, even following mild head injury [1, 3,13,14,15]. In the present case, recurrent episodes of transient but reversible hemiparesis would be consistent with intermittent arterial spasm.…”
Section: Discussionmentioning
confidence: 55%
“…Krauss et al reviewed patients with hemidystonia following head trauma, and CT or MRI revealed that all of the patients had contralateral basal ganglia or pontomesencephalic lesions [2]. Secondary blepharospasm is also caused by infarctions in the thalamus [4], striatum [5], and brainstem [6].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary dystonia is well known subsequent to lesions of the basal ganglia [2], thalamus, or brainstem [3]. Hemidystonia defined as involuntary, sustained posturing of the unilateral arm, leg, and face sometimes occurs following head trauma, with the cause of the contralateral basal ganglia or pontomesencephalic lesions [2].…”
Section: Introductionmentioning
confidence: 99%
“…65,74,134 Posttraumatic dystonia is most commonly found in patients with injuries in the basal ganglia and thalamus. 25,67,75,92 Reduced inhibitory control in basal ganglia-thalamocortical motor loops 4 leading to hyperactivity in frontal motor areas has been suggested to result in dystonia, 23 but the mechanisms of posttraumatic dystonia are complex, as different injury constellations will produce different dystonic symptoms.…”
Section: Dbs For Posttraumatic Dystonia and Parkinsonismmentioning
confidence: 99%